Cavitation Bubbles Remove and Inactivate Listeria and Salmonella on the Surface of Fresh Roma Tomatoes and Cantaloupes - Lee, Joshua J.; Eifert, Joseph D.; Jung, Sunghwan; Strawn, Laura K. (Frontiers in Sustainable Food Systems, 2018)
Raw produce has frequently been identified as the source of bacterial pathogens that can cause human illnesses, including listeriosis and salmonellosis. Microbial pathogens may attach and form biofilms on raw fruit surfaces and can be difficult to remove. A cavitation process (injection of bubbles into water) was studied for its effectiveness for removal and inactivation of Listeria monocytogenes and Salmonella Newport from the surfaces of fresh Roma tomatoes and cantaloupes. Individual fruit were separately inoculated with each pathogen, then submerged in a water tank and treated with a bubble flow through an air stone using one airflow rate (0–14 liters/min.) for up to 60 s. As airflow increased, L. monocytogenes reduction on tomato and cantaloupe surfaces increased up to 1.2 and 0.8 log CFU/fruit greater than with water alone (no bubbles), respectively. With a 14 L/min flow rate, Salmonella reduction on tomato and cantaloupe surfaces increased up to 0.9 and 0.7 log CFU/fruit greater than when no bubbles applied, respectively. Also, with the bubble treatments, additional pathogen reduction (detached organisms) was observed in the tank water. Therefore, these bubble streams can be used to enhance the detachment of bacteria from fruit surfaces and to inactivate a proportion of these detached microorganisms. Additionally, recoveries of Salmonella from inoculated Roma tomatoes and cantaloupe were determined for treatment water that contained 50 or 150 ppm sodium hypochlorite. Combining both cavitating bubbles and 150 ppm chlorine in the tank water resulted in greater efficacy of removing or inactivating S. Newport from the surface of cantaloupe (2.9 log CFU) than with cavitation (2.5 log CFU) or chlorine (1.9 log CFU) alone. The physical force of a bubble stream on raw produce can effectively detach and inactivate surface bacteria, and has the potential to reduce antimicrobial chemical use and water use in post-harvest packing operations.